Interaction between ischemia-reperfusion injury and intestinal microecology in organ transplantation and its therapeutic prospects - Lian, Yong-qi; Li, Peng-fei; Guo, Yan; Tao, Yan-lin; Liu, Ya-nan; Liang, Zhao-yu; Zhu, Shu-fen (Frontiers in Immunology, 2024)
Organ transplantation is a vital intervention for end-stage organ failure; however, ischemia-reperfusion injury is a complication of transplantation, affecting the prognosis and survival of transplant recipients. As a complex ecosystem, recent research has highlighted the role of the intestinal microecology in transplantation, revealing its significant interplay with ischemia-reperfusion injury. This review explores the interaction between ischemia-reperfusion injury and intestinal microecology, with a special focus on how ischemia-reperfusion injury affects intestinal microecology and how these microecological changes contribute to complications after organ transplantation, such as infection and rejection. Based on a comprehensive analysis of current research advances, this study proposes potential strategies to improve transplant outcomes, offering guidance for future research and clinical practice.